Pengembangan Sistem Penyimpanan Data Berbasis MongoDB dan GridFS Untuk Menyimpan Data Yang Beragam Dari Node Sensor - Gabreil Arganata; Eko Sakti Pramukantoro; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet of things (IoT) plays an important role in the development of the Internet today. The implementation, which resulted into IoT's heterogeneous data from variety of sensors, and it will keep getting bigger everyday. The examples of heterogeneous data are temperature, humidity, and image file. Along with that, problem of choosing which method to store the data into data storage appear. Based on that problem, the solution that's possible to be applied is NoSQL method. Therefore, in this research a media storing system using MongoDB and GridFS (NoSQL database) based are proposed to answer those challenges. Furthermore, an Internet Gateway Device is proposed to connect an existing middleware with data center. The solution are wrapped inside a framework which also include a web service to ease the request and response process. The system performance test has been done in few aspect such as functional, scalability, response time of saving and retrieving data, also analysis performance of data storage. The result of the functional test is that data storage system, which has been developed, is running well based on its function in storing variety of data into data storage. Based on those results, this system can become a solution for IoT data storage problem